PENGARUH VARIASI SUHU PENGERINGAN DALAM PEMBUATAN AMILUM TALAS KIMPUL (Xanthosoma sagittifolium (L.) Schoot) DENGAN OVEN - Yanti, Ni Made Frida; Putra, I Gusti Ngurah Agung Dewantara (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Kimpul taro (Xanthosoma sagittifolium) has a very high starch content of 68.50%. The starch content of taro taro can be used as an additive in the pharmaceutical field. The drying temperature used for the manufacture of taro kimpul starch must be precise and provide good pharmaceutical properties according to requirements. Tests for the physical properties of starch carried out in this study were identification tests, organoleptic tests, microscopic tests, drying shrinkage tests and pH tests. The test results show that the test helps produce a blue color, the organoleptic test produces starch that is white, odorless, and tasteless, with a microscopic round shape, has a hilum in the middle and lamellae that are not very clear, the drying temperature with an oven affects the physical properties starch. Increasing the drying temperature results in an increase in pH, and a decrease in the drying rate of milk.